Effect of nanosize MgO addition on the texture and mechanical strength of Bi-2212 superconductor compound - Hamid N.A.; Shamsudin N.F. (2023)
The Bi 2Sr 2CaCu 2O 8 (Bi-2212) high-temperature ceramic superconductor has the potential to be applied in power system applications due to its low thermal conductivity. However due to the material's brittle nature and low strength, reinforcement of the Bi-2212 superconductor is necessary for such applications. Due to its high melting point and lower heat capacity, magnesium oxide (MgO) is an excellent candidate as the reinforcement material. In this study, 3% to 8% weight percentage of nanosize MgO powder was added to Bi-2212 superconductor. The Bi-2212/MgO compounds were palletized and heat treated, followed by partial melting and slow-cooling. X-ray diffraction (XRD) was used to study the phases present in the samples. Scanning electron microscopy (SEM) with energy dispersive X-ray (EDAX) analysis was performed to investigate the microstructure, and for identifying the elemental composition of the samples. Electrical resistance and critical current density (J c) measurements were carried out using the standard four-probe dc method. The degree of texturing of the microstructure was determined using the texture coefficient calculations. In addition, the mechanical strength of the samples was studied by conducting compression test. The results show that the addition of small amount of MgO particles has improved the texture of the Bi-2212/MgO compound. The compound with 5% MgO addition shows significantly higher strength. Addition of higher than 8% of MgO has resulted in highly porous microstructure and subsequently decreasing the strength of the Bi-2212/MgO compound. (2012) Trans Tech Publications, Switzerland.